Financial reputation repair through environmental performance: A study of restatements in polluting industries. Issue 5 (4th November 2019) - Matozza, Felice; Biscotti, Anna Maria; Mafrolla, Elisabetta
Abstract : Purpose: This paper aims to examine whether firms in polluting industries improve their environmental performance to effectively repair their financial reputation in the aftermath of an accounting restatement – a financial reputation-damaging event. Design/methodology/approach: The authors test their hypotheses using multiple regression analysis of a sample of firms listed in International Financial Reporting Standards (IFRS)-adopting countries. They use a comparative empirical design in which a sample of firms that underwent a restatement (henceforth, restating firms) are compared with control groups of pair- and multiple-matched firms that did not undergo restatements (non-restating firms). Findings: The study finds that restating firms have higher environmental performance in the aftermath of restatement events. Additionally, the authors demonstrate that this environmentally based reputation repair positively influences the financial reputation of the firms, as measured by analyst coverage and recommendations and which previously decreased because of the restatement event. Practical implications: Because environmental levers are a substantial contextual factor in polluting industries, shifting the stakeholder debate to firms' environmental commitment can improve financial stakeholders' opinions and favour the repair of the multifaceted reputation of the financially damaged firm. Social implications: With a worldwide growing attention to environment there is a critical need for understanding how polluting firms integrate sustainability and financial reputation. We demostrate that polluting firms recover from a financial failure pursuing their environmental performance. Originality/value: Contributing to the behavioural theory of reputation repair and in line with the legitimacy perspective in environmental disclosure research, this paper shows that polluting firms recover from a loss to their financial reputation by diverting stakeholders' attention towards the environmental field, thus restoring their financial reputation, as financial analysts value environmental performance improvement – a substantial contextual factor of polluting firms' reputation repair process.